2021
DOI: 10.3390/nu13113898
|View full text |Cite
|
Sign up to set email alerts
|

Common Bean Baked Snack Consumption Reduces Apolipoprotein B-100 Levels: A Randomized Crossover Trial

Abstract: Snack alternatives based on common beans (Phaseolus vulgaris L.) have been developed to promote pulse consumption. The purpose of this study was to evaluate the chemical composition, sensory acceptance and the effect of common bean baked snack (CBBS) consumption on blood lipid levels in participants with overweight and altered blood lipid levels. A sensory evaluation by 80 untrained judges was carried out using a hedonic scale. A randomized crossover 2 × 2 trial was performed, where 20 participants with overwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 47 publications
0
19
0
Order By: Relevance
“…Eight studies assessed the effect of dark chocolate or cocoa supplementation in overweight/obese patients [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. Two studies analyzed the outcome of common bean or Phaseolus vulgaris consumption in the condition of T2DM and obesity [ 37 , 38 ]. Three studies evaluated the effect of avocado ingestion on abdominal adiposity and visceral adiposity in subjects with syndrome metabolic disease and obesity [ 39 , 40 , 41 ].…”
Section: Results Of the Systematic Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…Eight studies assessed the effect of dark chocolate or cocoa supplementation in overweight/obese patients [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. Two studies analyzed the outcome of common bean or Phaseolus vulgaris consumption in the condition of T2DM and obesity [ 37 , 38 ]. Three studies evaluated the effect of avocado ingestion on abdominal adiposity and visceral adiposity in subjects with syndrome metabolic disease and obesity [ 39 , 40 , 41 ].…”
Section: Results Of the Systematic Reviewmentioning
confidence: 99%
“…Patient anthropometric outcomes and serum lipid parameters enlisted in included studies are shown in detail in Table 2 . Two out of the fifteen studies were double-blinded, randomized, placebo-controlled trials with parallel groups [ 29 , 30 ]; two studies were randomized crossover trials [ 37 , 43 ]; two studies had a randomized, placebo-controlled, double-blind design [ 35 , 38 ]; one study had a multicenter, randomized, controlled parallel-arm trial design [ 40 ]; one study was a single-center, randomized, 2-arm, controlled, parallel trial [ 41 ]; three studies were randomized controlled trials [ 31 , 34 , 39 ]; one study was a randomized, placebo-controlled, cross-over [ 36 ]; one study was a double-blind, placebo-controlled, clinical pilot trial [ 32 ]; one study was a prospective dietary intervention [ 42 ]; and finally, one study was a two-phase, randomized, double-blind, clinical trial [ 33 ]. Most of them included adults of both genders, while one study included exclusively women.…”
Section: Results Of the Systematic Reviewmentioning
confidence: 99%
See 3 more Smart Citations